The Elderly Alzheimer Patient’s Portable Tools for Position Detection with SMS Notifications - Yulastri Yulastri; Era Madona; Anggara Nasution; M. Irmansyah (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
In this study we propose a portable tool to monitor and monitor patients at risk of Alzheimer's. The aim of this research was design and make a useful tool to determine the position and condition of Alzheimer's sufferers. The research stages consisted of designing hardware, software and testing the whole tool. The patient's condition find out by an accelerometer sensor was used which read the values of the x, y, and z axes to determine the condition of patient normal or falling. This tool also have a panic button which use by the patient if he did not know his position and forget the way to go home and SMS notification will be sent to the colleague when this button was pressed. The results of the test show the device can send an SMS notification of the patient's position when the supervisor sends a sms "GPS ON” and the navigation module can determine the location of the position. The distance between reading position of the GPS module to the test point in average was 2.39 meters. Generally speaking, the tool can working properly.